2005
DOI: 10.1007/s00701-004-0441-y
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and prevention of fatal head injuries in Germany – trends and the impact of the reunification

Abstract: Analysis of the admission/discharge data of all German hospitals reveals surprising inside views of age group-related incidence and mortality rates of head injuries in this country. Future research should be focused on patients with minor head injuries who account for nearly 200,000 cases of in-hospital treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 7 publications
4
46
0
3
Order By: Relevance
“…Forty-five per cent of the patients were in the lowest GCS group [3,4] (table 2). Half of the patients in the oldest population had a GCS of 3–4, and 20% of the patients had a GCS of 5–6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-five per cent of the patients were in the lowest GCS group [3,4] (table 2). Half of the patients in the oldest population had a GCS of 3–4, and 20% of the patients had a GCS of 5–6.…”
Section: Resultsmentioning
confidence: 99%
“…Prevention policies cannot be properly targeted without reliable data on the incidence, demography and external causes of injuries that aid in identifying the high-risk groups [2]. International epidemiological studies have reported changes during the last decades, with decreasing rate trends associated with TBI, incidence, hospitalizations and mortality [3,4]. The creation of regional trauma referral systems (level I trauma centres) and the introduction of standardized clinical procedures, such as guidelines that recommend transfer of severe TBI cases to neurosurgical centres irrespective of the need for neurosurgery, has resulted in significant reductions in TBI-associated mortality and morbidity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 gives an overview of 6 other studies conducted in Europe [15,16,17,18,19,20] reporting on the incidence of hospital admissions for TBI across shorter or longer time periods. These studies often focused on different time periods, thus making direct comparisons complex.…”
Section: Discussionmentioning
confidence: 99%
“…Die rasante technische Entwicklung im neurochirurgischen Operationssaal mit Hochleistungsmikroskopen und dem intraoperativen Ultraschall oder den intraoperativen Dopplersonographiegeräten hat entscheidend hierzu beigetragen. So lag die Mortalitätsrate in Deutschland 1972 bei 27,2 pro 100.000 Einwohner und 2000 bei 9 Sterbefällen pro 100.000 Einwohner [22]. Auch nach den Ergebnissen der National Data Trauma Bank (www.facs.org/trauma/ntdb/index.html), dem IMPACT (www.tbi-impact.org), den WHO-Daten [26] und prospektiven bzw.…”
Section: Schlussfolgerungenunclassified